REVIEW OF NASAL CHANGES WITH MAXILLARY ORTHOGNATHIC SURGERY - Leila KHAMASHTA-LEDEZMA; Farhad B. NAINI; Mehmet MANISALI (Istanbul University, 2017)
This article reviews the literature on nasal changes with maxillary orthognathic surgery. Understanding such changes is vital for surgical planning and for obtaining appropriate informed consent, and there are medico-legal implications. During orthognathic surgical planning a prediction of the effects of the different surgical movements is possible and this forms part of the basis of the planning stage. The predicted changes need to be identified and their desirability or not for each individual patient determined. Some techniques for managing undesirable nasal changes are discussed, including adjunct measures to minimize these potential effects (e.g. cinch sutures), and additional surgical procedures to manage the undesired nasal changes once they are produced.